IL‐33 delivery induces serous cavity macrophage proliferation independent of interleukin‐4 receptor alpha. Issue 10 (October 2016) - Jackson‐Jones, Lucy H.; Rückerl, Dominik; Svedberg, Freya; Duncan, Sheelagh; Maizels, Rick M.; Sutherland, Tara E.; Jenkins, Stephen J.; McSorley, Henry J.; Bénézech, Cécile; MacDonald, Andrew S.; Allen, Judith E.
Abstract : In vivo delivery of IL‐33 induces the proliferation of macrophages independent of the IL‐4Rα. Allergic inflammation causes serous cavity macrophage proliferation that is independent of either the IL‐4Rα or the IL‐33R. In the context of nematode infection, allergic airway inflammation or IL‐33 delivery, both receptors are required for alternative activation. Abstract : IL‐33 plays an important role in the initiation of type‐2 immune responses, as well as the enhancement of type 2 effector functions. Engagement of the IL‐33 receptor on macrophages facilitates polarization to an alternative activation state by amplifying IL‐4 and IL‐13 signaling to IL‐4Rα. IL‐4 and IL‐13 also induce macrophage proliferation but IL‐33 involvement in this process has not been rigorously evaluated. As expected, in vivo delivery of IL‐33 induced IL‐4Rα‐dependent alternative macrophage activation in the serous cavities. IL‐33 delivery also induced macrophages to proliferate but, unexpectedly, this was independent of IL‐4Rα signaling. In a filarial nematode infection model in which IL‐4Rα‐dependent alternative activation and proliferation in the pleural cavity is well described, IL‐33R was essential for alternative activation but not macrophage proliferation. Similarly, during Alternaria alternata induced airway inflammation, which provokes strong IL‐33 responses, we observed that both IL‐4Rα and IL‐33R were required for alternative activation, while macrophage proliferation in the pleural cavity was still evident in the absence of either receptor alone. Our data show that IL‐33R and IL‐4Rα promote macrophage proliferation independently of each other, but both are essential for induction of alternative activation.